Dashboard Monitoring dan Sistem Rekomendasi Hama Padi Berbasis Internet of Things untuk Petani (Studi Kasus: Tempuran) - Fitria Novyanti Taufik; Oman Komarudin; Carudin Carudin (Jurnal Ilmiah Wahana Pendidikan, 2026)
Pest attacks on rice crops are one of the main causes of agricultural productivity decline in Tempuran District, Karawang Regency. Manual pest monitoring leads to delays in control measures, particularly for brown planthoppers, rats, and birds. This study aims to design and implement a responsive web-based monitoring dashboard and recommendation system designed to integrate with Internet of Things (IoT) devices to support farmers' decision-making. The system was developed using the Software Development Life Cycle (SDLC) method with a Prototype model and built on the MERN Stack. System evaluation was carried out using Black-box Testing and User Acceptance Testing (UAT) involving farmers in Tempuran District. The results show that the system successfully displays real-time pest detection information, attack history and graphs, alert notifications, and rule-based pest control recommendations, with a user acceptance rate of 96% from six respondents. This study contributes as a foundation for local data-driven smart farming development, providing a pest monitoring interface for farmers that is ready to be integrated with IoT devices in further development.